2020
DOI: 10.36227/techrxiv.12212516
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leveraging Data Science To Combat COVID-19: A Comprehensive Review

Abstract: <div>COVID-19, an infectious disease caused by the SARS-CoV-2 virus, was declared a pandemic by the World Health Organisation (WHO) in March 2020. At the time of writing, more than 2.8 million people have tested positive. Infections have been growing exponentially and tremendous efforts are being made to fight the disease. In this paper, we attempt to systematise ongoing data science activities in this area. As well as reviewing the rapidly growing body of recent research, we survey public datasets and r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 48 publications
(50 reference statements)
0
46
0
Order By: Relevance
“…The data and code can be found at. 28 The study found that before the implementation of travel restrictions, the spatial distribution of COVID-19 can be highly correlated to mobility. However, the correlation is lower after the imposition of travel restrictions.…”
Section: Covid-19 Npi Analysismentioning
confidence: 93%
See 4 more Smart Citations
“…The data and code can be found at. 28 The study found that before the implementation of travel restrictions, the spatial distribution of COVID-19 can be highly correlated to mobility. However, the correlation is lower after the imposition of travel restrictions.…”
Section: Covid-19 Npi Analysismentioning
confidence: 93%
“…ML, big data, and statistical techniques can be applied to the data sets for tasks related to prediction. Figure 1 illustrates a consolidated view of the taxonomy of COVID-19 open source data sets [13,28].…”
Section: Taxonomymentioning
confidence: 99%
See 3 more Smart Citations